2014
DOI: 10.1039/c4ra08607d
|View full text |Cite
|
Sign up to set email alerts
|

Thorough investigation of varying template combinations on SAPO-34 synthesis, catalytic activity and stability in the methanol conversion to light olefin

Abstract: Crystals of SAPO-34 molecular sieves were synthesized under hydrothermal conditions by using tetraethylammonium hydroxide, morpholine and a mixture of them as structure-directing agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…When TEAOH and Mor were combined as the binary OSDAs for the synthesis of SAPO-34, the obtained catalyst had a smaller crystal size and a larger surface area, thereby improving the performance of SAPO-34 catalyst in the methanol conversion reaction [17]. A similar behavior was reported by Sedighi et al [18] who used different combinations of TEAOH and Mor to synthesize SAPO-34 and obtained the catalyst with the most extended lifetime with optimal crystal size and acidity for MTO reaction. TEA is reported to favor the formation of a SAPO-5 impurity phase, although it costs considerably lower compared to TEAOH.…”
Section: Introductionsupporting
confidence: 76%
“…When TEAOH and Mor were combined as the binary OSDAs for the synthesis of SAPO-34, the obtained catalyst had a smaller crystal size and a larger surface area, thereby improving the performance of SAPO-34 catalyst in the methanol conversion reaction [17]. A similar behavior was reported by Sedighi et al [18] who used different combinations of TEAOH and Mor to synthesize SAPO-34 and obtained the catalyst with the most extended lifetime with optimal crystal size and acidity for MTO reaction. TEA is reported to favor the formation of a SAPO-5 impurity phase, although it costs considerably lower compared to TEAOH.…”
Section: Introductionsupporting
confidence: 76%
“…They do not show up in the computer models of these molecular sieves, i.e., they seem not to be associated with the structural Brønsted acidic sites. In the course of our literature survey we have found that those researchers who use DRIFT technique [31][32][33][34][35][36][37][38][39][40] generally find these bands more intense than those who use TR technique [41][42][43][44][45][46][47][48][49][50][51][52][53][54] . In case of the H-SAPO-34 most researchers assign the band near ~3680 cm -1 to surface P-OH vibration, following Peri's 55 early empirical assignment from the TR spectra of an amorphous AlPO 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The large external surface area of the extremely small particles limits the inner surface areas and reduces the number of available acid sites in the micropores that act as active sites. 38 Accordingly, the rapid deactivation of S6 might be related to its small particles with a higher external surface area observed in FESEM and BET analyses. It is noteworthy to mention that using industrial feed condition (72% methanol in water) resulted in the earlier catalyst deactivation as well as lower olens production.…”
Section: Catalytic Performance In the Mto Reactionmentioning
confidence: 94%